The Effects of Different Seaweed Doses on Yield and Nutritional Values of Hydroponic Wheatgrass Juice - Muhammet Karasahin (Turkish Journal of Agriculture: Food Science and Technology)
This research was conducted to determine the effects of different seaweed doses on yield and nutritional values of hydroponic wheatgrass (Triticum aestivum L.) juice in the climatization chamber of Karabuk University, Eskipazar Vocational School, Department of Crop and Animal Production between the dates of 15.01.2015 and 15.06.2015. In the research, four different seaweed doses (Control; 0, D1; 150, D2; 300, D3; 450 and D4; 600 ppm) and control were applied to irrigation water and their effects on the content of biomass rate, biomass and grass yield, grass juice yield and pH, plant height and root length, biomass and grass dry matter rate, grass juice energy and macronutrient values (protein, carbohydrate, fat, dietary fiber and ash) were analysed. According to the results, while the highest biomass and grass yield, plant height values were obtained from D1, D2, D3 and D4 treatments, the highest grass juice yield and root length were obtained from D3 treatment. The highest pH, grass dry matter content was obtained from control treatment. Seaweed dose treatments were not had influence on grass juice energy values. However, the rise in the grass juice yield was caused a rise in the total energy values in the unit area. D3 treatments can be recommendable to achieve the highest grass juice yield.